The Shadow of Aksai Chin: Historical Legacies and Contemporary Challenges in India-China relations - Chaudhary, Seema (International Journal of Engineering and Management Research, 2022)
The India-China border conflict, especially around the Aksai Chin region, has been a major challenge in the relationship between the two Asian powers. This research paper explores the historical background of the dispute, focusing on colonial-era borders, the 1962 war, and China's control over Aksai Chin. It highlights how the lack of a clearly defined border, along with different national interests, has continued to cause tension. The paper also studies recent military standoffs such as the Galwan Valley clash in 2020, and how both countries have responded to these events. In addition, the paper looks into China’s broader foreign policy strategies that affect its behavior on the border, including the Five Finger Policy, Salami Slicing, Cabbage Strategy, and Wolf Warrior Diplomacy. These approaches show how China mixes military, political, and economic tools to expand its influence. India’s response, including military readiness and stronger diplomatic ties with other countries, is also discussed. By examining both historical and current events, the paper aims to understand the roots of the conflict and suggest ways to reduce tensions. The research stresses the importance of peaceful dialogue, mutual understanding, and long-term strategies to maintain regional stability and avoid future conflicts.